A case study of an integrated rice mill farm complex - Ullah, Md. Wali; Edwards, Peter; Singh, Gajendra; Vokes, Richard W. A.; Royal Danish Government (Bangkok : Asian Institute of Technology, 1979)
This research studies the different subsystems of an integrated rice mill farm complex with a view to finding their extent of dependence in terms of wastes utilization effectiveness. The objective of the research was also to formulate some dynamic model which may help the decision makers for policies. The study consists of a brief description of the different subsystems of the rice mill which include -parboiling, milling, brick manufacture, and oil extraction and for the farm-poultry, piggery, aquaculture and agriculture; a system dynamics study which is concerned with the formulation of dynamic models, and then the simulation by computer. From this study it is found that the wastes are being used very effectively. The company has scope to earn enough money by utilizing husk ash and bran for producing bricks and oil respectively. In the farm aquaculture gives more profit than pigs and ducks. Finally, for different combinations of farming for 0.1 ha farm pond recommended number of animals have been quoted which is shown in Table 14.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1979
Keywords: Rice -- Milling; Farms -- Thailand; Aquaculture